2015
DOI: 10.1186/s13006-015-0044-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of discontinuing exclusive breastfeeding before six months among mothers in Kinshasa: a prospective study

Abstract: BackgroundAlthough breastfeeding is common in Democratic Republic of the Congo, the proportion of women who exclusively breastfeed their babies up to 6 months remains low. This study aimed at identifying predictors of discontinuing exclusive breastfeeding before six months among mothers in Kinshasa.MethodsA prospective study was carried out from October 2012 to July 2013 among 422 mother-child pairs recruited shortly after discharge from twelve maternities in Kinshasa and followed up to six months. Interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
98
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(120 citation statements)
references
References 29 publications
14
98
2
6
Order By: Relevance
“…Our EBF findings were similar to a study in Addis Ababa, Ethiopia which found 29.3 % prevalence of EBF under six months [9], while it was higher than a study in Abha female educational district, Saudi Arabia in which EBF for 6 months was reported only by 8.3 % of participants (n = 32) [6] and a study in Kinshasa, Congo that found only 2.8 % of infants were exclusively breastfed (n =12) [7].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our EBF findings were similar to a study in Addis Ababa, Ethiopia which found 29.3 % prevalence of EBF under six months [9], while it was higher than a study in Abha female educational district, Saudi Arabia in which EBF for 6 months was reported only by 8.3 % of participants (n = 32) [6] and a study in Kinshasa, Congo that found only 2.8 % of infants were exclusively breastfed (n =12) [7].…”
Section: Discussionsupporting
confidence: 74%
“…In Saudi Arabia only by 8.3 % (n = 32) of the 384 participants EBF for 6 months [6]. In a study in Congo, 87.5 % of infants were EBF during the maternity stay, but by six months, only 2.8 % (n = 12) of infants were exclusively breastfed [7]. In a study done in Nigeria, the majority (88.0 %) of the respondents had heard about EBF and hospital was the source of information, and more than 50 % of the women had a positive attitude towards breastfeeding [8].…”
Section: Introductionmentioning
confidence: 99%
“…Definitions of maternal knowledge of EBF varied across studies and included: maternal report of EBF definition and related benefits, recommendations and/or best practices. Only three studies found a significant association between maternal knowledge and EBF practices (12,23,24) . In Ethiopia, a large cross-sectional study found that mothers with low knowledge of breast-feeding 'best practices' had 3·4 times higher odds of non-EBF than mothers with high knowledge of breast-feeding best practices (12) .…”
Section: Prenatal-related Barriers To Exclusive Breast-feedingmentioning
confidence: 99%
“…Arusei et al (29) 151 Kenya Longitudinal X Aubel et al (57) 260 Senegal Mixed methods Babakazo et al (24) 422 DRC Cohort Chandrashekhar et al (11) 385…”
mentioning
confidence: 99%
See 1 more Smart Citation